Discounting and welfare analysis over time: choosing the [eta] - Wolfgang Buchholz; Jan Schumacher (Center for Economic Studies and ifo Institute (CESifo), 2008)
Based on the Ramsey equation and an ethically motivated rejection of pure utility time discount, the Stern Review on the Economics of Climate Change concentrates on the use of the elasticity of marginal utility ç in the intergenerational social welfare function. We support this position by showing that, also from the view point of sustainability, application of ç is preferable to the use of the pure time discount parameter \~n when a balanced distribution of utility across generations is to be brought about. After reviewing empirical studies on the size of ç we develop a novel axiomatic approach based on non envy criteria by which we obtain values for ç lying in a range between 1 and 2. Whereas the starting point of the Stern Review quite explicitly is an ethical one, many critics of the Review deny this ethical stance and thus - as described in our paper - miss a crucial element of the Stern Review
Keywords: D6; D9; Q5; 330; Ramsey equation; discounting; sustainability; non-envy; Soziale Diskontrate; Zeitpräferenz; Second Best; Soziale Wohlfahrtsfunktion; Theorie